Onomástica em Libras de Formosa-GO - Chaibue, Karime (2022)
This study aims to describe and analyze structural and motivational aspects of onomastic signs in Brazilian Sign Language (Libras), relating to the city of Formosa, state of Goiás, Brazil. In this sense, there was the survey, recording and analysis of place signs (called toponyms), and people signs (called antroponyms). The onomastic signs were first categorized according to morphological formation, form, and motivation, according to the proposal by Miranda (2020). There was also an investigation about the frequency of the points of articulation in the signs' constitution. Within the morphological category related to morphological category, the signs were classified as simple or compound. Concerning the form, they were divided into native, initialized, or spelled. With respect to motivation, both iconic motivation (constituted by material or cultural aspect) and Portuguese language motivation (related to the spelling or the decal process) were presented. The categories related to the signs' morphological formation and form are exclusive, while the motivations can present an accumulative character in the signs. The toponyms gather a quantitative of 32 signs, and the anthroponyms, a total of 109 signs; they, thus, form a corpus of 141 onomastic signs. After the analysis of the onomastic data in general, a detailing of their motivational unfoldings was traced according to their specificity, whether toponyms or anthroponyms. The anthroponymic signs were also analyzed according to the taxonomic perspective by Barros (2018). The research methodology followed a qualitative approach, thoroughly investigating the linguistic and extralinguistic motivations of the signs. Data were made explicit by the application of interviews in Brazilian Sign Language (Libras) and by video recording of onomastic signs with the participants. The present research has an ethnographic bias, contemplating several periods of immersion of the researcher in the deaf community of Formosa, state of Goiás. The research participants were 13 adults, who belong to the deaf community of this city, with 10 (ten) deaf people and and 3 (three) listeners. We noticed in our corpus the predominance of simple signs and iconic motivations; however, motivations with more than one aspect were also productive. With regard to form, the toponyms presented a greater recurrence of initialized signs, and the anthroponyms, of native signs. The most frequent point of articulation among the toponyms was the neutral space; among the anthroponyms, the face. We could verify the need to include new motivational subdivisions, both for toponyms and anthroponyms, in order to contemplate the specificities of the collected data. This research contributes to deepen the descriptive studies in Brazilian Sign Language (Libras), broadening a discussion about onomastics, valuing the cultural aspects in linguistic analysis and bringing more visibility to the deaf community of Formosa, state of Goiás.